2019
DOI: 10.1016/j.scienta.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solid and liquid digestate for hydroponic baby leaf lettuce (Lactuca sativa L.) cultivation

Abstract: Digestate was evaluated as an alternative and sustainable growing medium and nutrient solution in the hydroponic cultivation of baby leaf lettuce (Lactuca sativa L.). Nine hydroponic combinations of substrate and fertilization (agriperlite + standard solution, agriperlite + liquid digestate, solid digestate + standard solution, solid digestate + liquid digestate, soil + standard solution, peat moss + standard solution; peat moss + liquid digestate, pelleted digestate + standard solution and pelleted digestate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 58 publications
3
44
0
6
Order By: Relevance
“…Therefore, digestate could be interesting as a sustainable fertilizer for crop production. Ronga et al [23][24][25] suggested the use of digestate as innovative fertilizer and growing media for the production of basil, peppermint, baby leaf lettuce and grapevine in soilless cropping systems. Other researches highlighted improving in quality and yield of digestate-fertilized crops.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, digestate could be interesting as a sustainable fertilizer for crop production. Ronga et al [23][24][25] suggested the use of digestate as innovative fertilizer and growing media for the production of basil, peppermint, baby leaf lettuce and grapevine in soilless cropping systems. Other researches highlighted improving in quality and yield of digestate-fertilized crops.…”
Section: Introductionmentioning
confidence: 99%
“…Vineyard winter pruning wood is usually destroyed by infield burning or crushing onto the soil, and the same occurs for grape stalks. On the other hand, a better valorization of vineyard pruning and winery out stream as feedstock for biogas plants [21][22][23] and pyrolysis [24] might increase vineyard sustainability providing green energy and promising fertilizers, such as digestate and biochar [25]. Considering that little information is reported on the use of compost and biochar coming from the valorization of vineyard by-products, the present study aimed to close the waste cycle in vineyards via the reuse of by-products.…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating the fertilizer value of digestate from sugar beet pulp has shown that mineral fertilizer can be substituted to fertilize sugar beets [37]. The effect of solid and liquid digestate was investigated in a hydroponic system to cultivate baby leaf lettuce and the results showed that the investigated forms of digestate (solid and pelleted forms as well as the liquid fraction with agriperlite) represent an alternative growing media in hydroponic systems [38]. Digestate can also be used for algae production [35].…”
Section: Introductionmentioning
confidence: 99%